Book Review. The Broadcasted Future of Sport Management. Branden Buehler’s Front Office Fantasies. The Rise of Managerial Sports Media (Papers in Arts and Humanities, 2025)
Branden Buehler's book deals with sports management and media and the relation between these notions. Its bibliography is large, as a result of extensive research that started, according to the author, while he was in graduate school. The research was developed into the current volume due to the help and influence of a series of people. Highly enjoyable to read, this book adopts a unique focus on certain issues related to the social character of the phenomenon mentioned above.
Keywords: sports media; sports management; philosphy of sports